Rural and remote communities as non-state actors : a legal and moral argument - Radavoi, Ciprian Nicolae; Price, David, 1948- (Routledge, 2023)
"While entities as different as armed groups, multinational corporations, political parties, megacities, labour unions, terrorist organisations or indigenous peoples are mentioned as Non-State Actors in the relevant literature, rural communities are never referred to"-- Provided by publisher.
Keywords: Non-state actors (International relations); Rural development -- Law and legislation.; Rural conditions -- Political aspects.; LAW / International